System and method for pulverizing a substance - RUSSELL STEVEN CRAIG; MITCHELL CHARLES MARTIN; VILLA CHRIS J; RUSS FREDRIC S (2014)
Embodiments of the present disclosure are directed to a fuel preparation system. The feedstock preparation system includes an acoustic chamber configured to receive a fuel and at least one acoustic wave generator configured to generate acoustic waves to at least partially break up the fuel in the acoustic chamber.